2012
DOI: 10.1186/2162-3619-1-25
|View full text |Cite
|
Sign up to set email alerts
|

BIRC6 (APOLLON) is down-regulated in acute myeloid leukemia and its knockdown attenuates neutrophil differentiation

Abstract: BackgroundInhibitors of apoptosis (IAPs) were intensively investigated in the context of cancer where they promote tumor growth and chemoresistence. Overexpression of the IAP BIRC6 is associated with unfavorable clinical features and negatively impacts relapse-free survival in childhood acute myeloid leukemia (AML). Currently, BIRC6 levels in adult primary AML have not been compared to the expression in normal myeloid cells. Thus, we compared for the first time BIRC6 levels in adult primary AML patient samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This finding suggests that AHR is an important regulator of genes which control ROS detoxification, as Stra13 has been decreased in both AhR-KO and AhR Vav1 mice. Birc6 is a regulator of apoptosis and has been described as being deregulated in acute myeloid leukemia [ 44 ]. Interestingly, knockdown of Birc6 in cell lines used to model promyelytic leukemia impairs neutrophil differentiation, and AhR regulation of Birc6 is suggested by our data.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that AHR is an important regulator of genes which control ROS detoxification, as Stra13 has been decreased in both AhR-KO and AhR Vav1 mice. Birc6 is a regulator of apoptosis and has been described as being deregulated in acute myeloid leukemia [ 44 ]. Interestingly, knockdown of Birc6 in cell lines used to model promyelytic leukemia impairs neutrophil differentiation, and AhR regulation of Birc6 is suggested by our data.…”
Section: Discussionmentioning
confidence: 99%
“…PML-RARα is a potent transcriptional repressor in APL cells, and it blocks promyelocyte differentiation. An interesting characteristic of this oncogenic protein is that its transcriptional repression effects can be reverted with pharmacologic doses of ATRA, resulting in the reactivation of genes essential for definitive myeloid differentiation [ 2 , 3 , 25 ]. Recently, lncRNAs have been shown to be dysregulated in various cancers, and several lncRNAs have been functionally linked to cancer and cell differentiation [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the previous observations that BIRC6 upregulation was also resistant to various anticancer drug in different cancer cells 31,35–37 , the effect of miR-204 on apoptosis through BIRC6 was further confirmed in our study using BIRC6 plasmid in AML cells. However, a previous study reported that reduced BIRC6 expression was associated with an immature myeloid phenotype of AML samples rather than immature myeloid cells 38 . These apparent discrepancies may be related to different cell subtypes in distinct leukemic entities and must be reconciled by additional studies.…”
Section: Discussionmentioning
confidence: 89%